Violence in privacy, Gender and Human Rights: expressions of youth in educational context - Costa, Aline Moerbeck; Cavalcanti, Vanessa Ribeiro Simon (Revista Jurídica Portucalense, 2019)
Abstract: In contexts of rape and abusive relationships, analyzing the violence in intimacy relations, with generational cut in youth from the perspective of Human Rights and gender, is the central focus. The issue has reached visibility, at the social and scientific levels, being considered as a problem and one of the current urgencies, due to the multiplicity of manifestations and consequences. Therefore, mapping violent occurrences in the intimacy relations of / among young people, in addition to listing the main legal elements of protection and defense, in light of the literature composes scope of the article. As a methodological approach, the study was carried out with two young men and women, aged between 16 and 24 years, from two middle-sized public schools in the municipalities of Bahia (Salvador and Feira de Santana). It was used as instrument "Young Loving Trajectory \ PAJ" (original from Canada - Parcour amoreux des jeunes), Brazilian version, to operationalize the qualitative approach (interviews - subjective questions). The need for effective investments, sensitizing family and educational contexts (prevention and information), from different social sectors to the importance of intimate relationships among young people, was concluded. Other results point to the construction of projects based on awareness and education for and by the Rights of youth, informing, understanding and avoiding abusive relationships. Keywords: violence; youth; intimacy; social and family context; human rights; citizenship.